Punishing benevolence: the criminalization of homeless feeding as an act of state harm - Dum, Christopher P. (Critical criminology, 2017)
The homeless population in the United States increased substantially since the 1980s. As a result, research into homelessness and its effects, as well as policies aimed at addressing this vital social problem, have also grown. While criminologists have examined state actions to control the homeless from a critical perspective, we are not aware of any research that addresses the issue of restricting homeless feeding. Because such state actions extend the criminal justice system by criminalizing benevolent acts, restrictions on feeding the homeless are ripe for critical examination. In this article, we examine such restrictions in American cities and argue that they can be conceptualized as a form of state harm. These government practices target homeless advocates engaged in charitable work by prohibiting feeding in particular locations and/or requiring expensive permits and licenses in order to provide food. Using the theoretical framework of state crime we argue that these policies are a recent evolution of laws that target the homeless, and suggest that these polices represent a disturbing trend of policies that attempt to regulate grassroots and community efforts to combat injustice and inequality. We finish by offering new directions for research and action in order to reduce the harm incurred by these policies.